Review of Cadmium Bioaccumulation in Fish Exposed to Cadmium - Ju-Wook Lee; A-Hyun Jo; Yue-Jai Kang; Dain Lee; Cheol-Young Choi; Ju-Chan Kang; Jun-Hwan Kim (Toxics)
Cadmium (Cd) is a highly toxic substance in the aquatic ecosystem, which can represent a high risk to fish. Fish are exposed to heavy metals through waterborne and dietary pathways, some of which are absorbed by the body and can accumulate in specific tissues without being eliminated. The accumulation varies depending on several factors such as dose, exposure route, exposure time, metal types, and biological status of the fish, and environmental parameters such as DO, salinity, pH, and metal speciation. As Cd speciation occurs in the water, the amount accumulated in the fish can vary, and consuming Cd-accumulated fish can pose a risk to human health. Cd introduced into the body of fish can directly affect blood properties through the circulatory system. Cd introduced into the circulatory system of fish can reach all tissues through the blood flow, and the accumulation of specific tissues is different depending on the blood flow by the energy and oxygen demand of each tissue. Therefore, this review aimed to determine the toxic effects of Cd exposure in fish and identify indicators to assess the extent of Cd bioaccumulation toxicity in fish induced by Cd exposure.